Análisis de la toma de decisiones a partir de la medición a costo atribuido en una pyme: del sector comercial. - Tello Serrano, José María; Ahumada Leguizamón, Diana Milena (Universidad Antonio Nariño, 2021)
The present investigation was carried out to obtain the title of Master in Financial and Tax Management. The work addresses a case study where an analysis of decision-making based on measurement at attributed cost is theoretically described to determine the most favorable impact on the equity of an SME´S. For this purpose, a research whose nature is mixed was used, where through the analysis and contrast of financial documents the differences in the implementation of the IFRS standard were measured; In coherence, a semi-structured interview was designed to analyze, in light of the theory consulted, the role of decision-making as an attributed cost and / or fair value. As a result, a detailed description of the financial condition and the elements of management competencies that were reflected in the financial reality of the company the business comunity were obtained.